(untitled) (Research, Society and Development, 2021)
Type 2 diabetes mellitus (DM2) is characterized by glucose intolerance and hyperglycemia, which favors the manifestation of oxidative stress and inflammation, conditions considered as one of the main factors involved in the pathophysiology of diabetic complications. Measures that can reduce oxidative stress and inflammation constitute a viable strategy for the control of DM2. The article aimed to identify the relationship between the antioxidant potential of pequi (Caryocar brasiliense Camb) and the prevention of the inflammatory/oxidative process present in DM2. This is a literature review of a narrative nature, in which a literature search was carried out from January to June 2021 in the PubMed, Scielo and CAPES journals databases, using the terms described in DeSC: Pequi, Type 2 Diabetes Mellitus, Inflammation and Oxidative Stress, in Portuguese, English and Spanish. From the reading, it was observed that pequi is a fruit rich in fatty acids, such as oleic, palmitic and stearic acids, and recent research indicates that this fruit also has significant amounts of carotenoids and phenolic compounds, demonstrating a strong natural antioxidant potential, with commercial properties, and possible exploitable technological and functional applications. The consumption of foods that are sources of antioxidants such as cerrado fruits, specifically pequi, can contribute to the prevention of the pathological cascade present in DM2, however more studies are needed to verify the influence of antioxidant compounds present in pequi oil on the antioxidant defense system and inflammatory activity in the presence of chronic hyperglycemia.